Developing a Culture of Safety Communication for Enhancing Risk Awareness in Industrial Workplaces - Hanifah Handayani (Education Achievement: Journal of Science and Research, 2025)
The increasing need to strengthen the safety culture in the industrial sector, especially in large industrial areas such as Karawang which has a high level of work risk and complexity of communication between organizational levels. A suboptimal safety communication culture often hinders the formation of worker risk awareness, so a deep understanding of how communication practices, organizational values, and daily interactions build or weaken awareness of occupational hazards. This study aims to analyze the process of developing a culture of safety communication and explain how safety communication patterns can increase risk awareness in industrial work environments. Using a qualitative approach of case studies on two manufacturing companies in Karawang, data was collected through in-depth interviews with 12 informants consisting of 2 HSE managers/staff, 4 production line supervisors, and 6 operators from various work units, accompanied by direct observation on safety briefing activities and K3 document review. Data were analyzed using thematic analysis techniques to identify patterns, barriers, and communication practices that affect workers' risk perceptions. The results show that an effective safety communication culture is built through active leadership involvement, open hazard reporting mechanisms, consistency of safety messages, and the use of communication media that is easy to understand across levels. In addition, risk awareness increases when communication is dialogical, routine, and integrated with the safety learning system. This study concludes that strengthening safety communication culture contributes significantly to increasing risk awareness and encouraging safe work behaviors, as well as providing practical implications for the development of organizational culture-based OSH strategies in the industrial sector.